THE RISKS ON THE RUSSIAN FINANCIAL MARKET IN THE CONDITIONS OF GLOBALIZATION - Olga Pakova; Anton Khasanov (Вестник Северо-Кавказского федерального университета, 2022)
The article considers topical issues of the functioning of the European market in a globalizing economy. The notion of «Euromarket», considers the types of transactions and loans in the Euromarket, the participants and direction of development. Identified major changes in operations on the Euromarket in the context of globalization, a share of participation of Bank of Russia and the national banks, the necessity of increase of efficiency offunctioning of the financial market in order to strengthen the international economic relations and increasing the volume of international trade in inancial instruments.